INFORMASI JASA LAUNDRY BERBASIS WEB - Alam, Syahirun; Yunus, Mughaffir; Irmah (Fakultas Teknik Universitas Muhammadiyah Parepare, 2021)
Laundry service information system that is applied at Syatifa Washing House aims to facilitate service to consumers who had consumers have to come to the place while bringing their laundyan goods, with this system is no longer necessary, from picking up to returning laundry items will be done by the courier from Syatifa Washing House. The system used is an online website based, on this website a list of laundry goods prices is also displayed so that customers who want to use our services can find out how much the estimated price will be paid if they use laundry services at Syatifa Washing House, if agreed with the price stated by the customer will be directed to make the registration process first to the Syatifa Washing House website. After that, ordering can be done, after ordering, a courier will arrive who will pick up customers' laundry items, in this process the customer can make payments according to the terterah price after weighing by the courier, then just wait for the goods to come back to be delivered by the courier .